A review of future directions in the development of sustainable carbon fiber from bio-based precursors. (December 2022) - Le, N.-D.; Varley, R.J.; Hummel, M.; Trogen, M.; Byrne, N.
Abstract: Carbon fiber (CF) is undoubtedly the structural material of the 21st century, but its usage remains limited to niche applications and high-value products due to its high production cost. Of the many challenges to reducing the cost of CF, low-cost precursors from renewable resources are a promising approach, simultaneously addressing both cost and sustainability. This paper, therefore, focusses on the challenges of manufacturing CF from lignin, cellulose, and blends thereof, with respect to spinning, stabilization, and carbonization. Strategies which address these challenges, including improving spinnability, increasing yield and the rate of stabilization, reducing fiber fusion, and optimizing the graphitic structure, are all discussed. Advanced bio-based precursors Lyocell, Ioncell® and emerging blended fibers are also introduced, including a discussion on their transformation into a new class of sustainable CF.